2014
DOI: 10.1002/2013jc009407
|View full text |Cite
|
Sign up to set email alerts
|

Wind-forced interannual variability of the Atlantic Meridional Overturning Circulation at 26.5°N

Abstract: , when the anomalous winddriven Ekman transport also has a significant contribution. The physical mechanisms for the interannual changes of the AMOC are proposed and evaluated in a two-layer model. While the Ekman transport is linked to the North Atlantic Oscillation (NAO), the anomalous geostrophic transport involves the oceanic adjustment to surface wind forcing. In particular, the intensification and weakening of the southward interior geostrophic flow is modulated by the internal Rossby wave adjustment to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
107
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(121 citation statements)
references
References 52 publications
9
107
0
Order By: Relevance
“…It is becoming clear that changes in the geostrophic contribution to the AMOC often involve a complex oceanic adjustment to the wind forcing. Zhao and Johns () show that most of the observed interannual variability in overturning and its components at 26°N can be reproduced in a linear, two‐layer model forced only by winds (Figure ).…”
Section: Monitoring and Understanding Observed Amoc Variability At 26°nmentioning
confidence: 99%
“…It is becoming clear that changes in the geostrophic contribution to the AMOC often involve a complex oceanic adjustment to the wind forcing. Zhao and Johns () show that most of the observed interannual variability in overturning and its components at 26°N can be reproduced in a linear, two‐layer model forced only by winds (Figure ).…”
Section: Monitoring and Understanding Observed Amoc Variability At 26°nmentioning
confidence: 99%
“…Huthnance (2004) indicated that coastal tide gauges can be especially effective monitors for the largest-scale oceanic signals. Zhao and Johns (2014) shows that wind-driven variations over the sub-tropical gyre can result in coherent variations along the GS path over thousands of kilometers, so that the open oceanshelf transmitting mechanism discussed by Huthnance seems possible for those GS signals. There are also some differences in the CTW's characteristics between waves with periods shorter or longer than ∼10 days, whereas in the higher frequency range, near-resonance CTW can amplify the coastal response (Huthnance 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The motivation for this study is twofold: First, the exact mechanism of the GS-driven CSL has not been completely explained or separated from other drivers of CSL. For example, coherent variations of CSL variations along the coast can also result from wind-driven sea level (Woodworth et al 2014;Zhao and Johns 2014) vertical divergence of large-scale ocean currents (Thompson and Mitchum 2014), from the impact of atmospheric pressure (Piecuch and Ponte 2015) or changes in the southward flowing Slope Current (Rossby et al 2010); changes in the latter may relate to climatic change in sub-polar regions (Hakkinen and Rhines 2004) or in the flow of coastal Labrador waters into the region (Xu and Oey 2011). Second, even if the GS contributes to variations in CSL, it is not clear on what time scales this driver may be valid.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical investigations into the sources of variability to the Atlantic MOC interannual variability suggest that much of the variability may be attributable to winds (Cabanes et al, 2008;Roberts et al, 2013;Zhao and Johns, 2014;Yang, 2015;Pillar et al, 2016). Buoyancy forcing instead affects decadal variations (Polo et al, 2014;Yeager, 2015).…”
Section: Introductionmentioning
confidence: 99%